Plagiarism in Political Culture. Political Discourse Analysis in the Context of Plagiarism Scandals of Contemporary Slovak Politicians - Kapráliková, Ivana, 1974-
Plagiátorské škandály vybraných súčasných slovenských politikov. Dôsledky prípadov plagiátorstva politikov v Európe.